Analysis on intra-aneurysmal flow influence by stenting - Wong, K.; Thavornpattanapong, P.; Tu, J.; Sun, Zhonghua (IEEE Engineering in Medicine and Biology Society, 2010)
This Using numerical simulation, the evolution of vortices in an aneurysm can be tracked. We examined large-scale swirling of blood within a significantly dilated aneurysm and quantified the pressure gradient and shear strain rate. Based on these fluid mechanical parameters, we are able to identify the difference in flow effects between the untreated and stented aneurysmal arteries. This study demonstrates that the large-scale vortex, pressure gradient and blood shear strain rate within an aneurysm sac reduces after stenting.